2020
DOI: 10.1007/s11145-020-10078-6
|View full text |Cite
|
Sign up to set email alerts
|

Does the availability of orthography support L2 word learning?

Abstract: Availability of orthography during word learning has been found to facilitate learning the word’s spelling and pronunciation and has been proposed to facilitate learning its meaning. This has not been studied in second language (L2) learning yet, in which word learning often corresponds to translation learning. Therefore, an L2 word learning experiment was carried out. Grade 6 Dutch students (n = 92) were taught English words, with orthography available or absent. Words were divided into those that are spelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
(84 reference statements)
3
12
0
Order By: Relevance
“…Overall results showed that learners in the RWL group recalled a significantly larger number of spoken word forms than learners in the LO group, which aligned with earlier research findings showing that reading with auditory support is an effective way to build form-meaning connection for L2 words (Brown et al, 2008;Bürki et al, 2019;Krepel et al, 2021;Malone, 2018;Webb & Chang, 2012). Also, learners in the RWL and LO groups produced L2 words in a manner that listeners perceived to be less accented and more comprehensible compared to words produced by learners assigned to the RO mode.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Overall results showed that learners in the RWL group recalled a significantly larger number of spoken word forms than learners in the LO group, which aligned with earlier research findings showing that reading with auditory support is an effective way to build form-meaning connection for L2 words (Brown et al, 2008;Bürki et al, 2019;Krepel et al, 2021;Malone, 2018;Webb & Chang, 2012). Also, learners in the RWL and LO groups produced L2 words in a manner that listeners perceived to be less accented and more comprehensible compared to words produced by learners assigned to the RO mode.…”
Section: Discussionsupporting
confidence: 85%
“…Unlike previous studies focusing on contextualized learning, Bisson et al (2014) had L2 beginners engage with a decontextualized activity (a letter-search task) where their attention was drawn to spellings of target words while receiving exposure to the spoken forms and pictorial information. In that study, as little as two exposures to the multimodal stimuli led to significant improvement of translation recognition accuracy (see also Krepel et al, 2021, for more evidence supporting multimodal effects on L2 vocabulary learning through a decontextualized activity using translation practice). The attested advantage of multimodal input over unimodal input aligns with the cognitive theory of multimedia learning (Mayer, 2014).…”
Section: Written and Spoken Input And L2 Vocabulary Learningmentioning
confidence: 81%
“…Similarly, Bürki et al (2019) found higher accuracy and faster response times for native French adults' learning of novel English words when the words were presented with their written forms compared to auditory presentation alone. In contrast, Krepel et al (2020) found that orthography helped primary school students with non-native word spelling and reading. These studies overall support that explicit word learning is facilitated when presented with additional sources of information or modalities, but whether the improvement in learning can be attributed to the mere presentation of orthography or whether it occurred purely because it is an additional modality remains unclear.…”
Section: Introductionmentioning
confidence: 84%
“…Previous studies have examined the role of orthographic information in word learning by presenting spoken words with or without their written forms. As reviewed by Bassetti et al, (2015) and Escudero (2015), orthographic input can either facilitate (Bürki et al, 2019;Escudero et al, 2008;Showalter & Hayes-Harb, 2013), or hinder (Bassetti, 2007;Hayes-Harb et al, 2010) word learning, while other studies have reported mixed effects or no effect at all (Escudero & Wanrooij, 2010;Krepel et al, 2020;Simon et al, 2010). For instance, Escudero et al, (2008) demonstrated that explicit learning of words containing non-native phonological contrasts was facilitated by the availability of orthography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation